2012
DOI: 10.5402/2012/659257
|View full text |Cite
|
Sign up to set email alerts
|

Method Development and Validation of Darifenacin in Rat Plasma by Liquid Chromatography-Tandem Mass Spectrometry: Application to a Pharmacokinetic Study

Abstract: A selective, sensitive, and high-throughput liquid chromatography-tandem mass spectrometry (LC-ESI-MS/MS) method has been developed and validated for the quantitation of darifenacin in rat plasma. Sample clean up involved liquid-liquid extraction (LLE) and used 100 µL of rat plasma. Zorbax, SB C18, 4.6 × 75 mm, 3.5 µm particle size analytical column using 10 mM ammonium acetate buffer (pH 5) and methanol (10 : 90, v/v) as the mobile phase was used. The parent → product ion transitions for the drug (m/z 427.3 →… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…[19] Therefore, this study was aimed at developing and validating a simple, rapid, and reliable UPLC-MS/MS method for tadalafil determination in human plasma that may have applications in pharmacokinetic, bioavailability, or bioequivalence studies.…”
Section: Transl Clin Pharmacolmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] Therefore, this study was aimed at developing and validating a simple, rapid, and reliable UPLC-MS/MS method for tadalafil determination in human plasma that may have applications in pharmacokinetic, bioavailability, or bioequivalence studies.…”
Section: Transl Clin Pharmacolmentioning
confidence: 99%
“…[11] In recent pharmacokinetic studies, LC-tandem mass spectrometry (LC-MS/MS) has primarily been used for measuring tadalafil in plasma because of its high sensitivity and selectivity. [12][13][14][15][16][17][18][19] Proença et al published a validated ultra-performance liquid chromatography (UPLC)-MS/ MS method for the analysis of sildenafil, vardenafil, and tadalafil in postmortem blood samples. [17] Lee et al also reported an LC-MS/MS method for the determination of five ED drugs and their selected metabolites in hair to monitor abuse of mirodenafil, sildenafil, tadalafil, udenafil and vardenafil.…”
Section: Introductionmentioning
confidence: 99%